2006
DOI: 10.1159/000089781
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease: Current Therapeutic Options

Abstract: Medical management of inflammatory bowel diseases (IBD) includes two treatment strategies: induction and maintenance of remission. 5-Aminosalycilates are mostly used for mild active IBD and for maintenance treatment in ulcerative colitis (UC). Glucocorticoids remain, despite their frequent (and occasionally severe) side effects, as the mainstay for induction of remission in moderate to severe active IBD, both UC and Crohn’s disease (CD). Cyclosporine and infliximab have emerged as the main, rapid-acting, alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 76 publications
0
38
0
1
Order By: Relevance
“…Although the development of therapeutic monoclonal antibodies is one of the most important advances in the care of IBD patients during the past decade, current therapies based on such biological agents are not entirely as effective as expected, as several untoward effects including immunogenicity, infusion reactions, and other serious adverse events have been reported. 13,16,17 Therefore, experimental approaches to develop new therapeutic options for IBD are encouraged.…”
Section: Effects Of Decoy Odns On Expression Of Proinflammatory Cytokmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the development of therapeutic monoclonal antibodies is one of the most important advances in the care of IBD patients during the past decade, current therapies based on such biological agents are not entirely as effective as expected, as several untoward effects including immunogenicity, infusion reactions, and other serious adverse events have been reported. 13,16,17 Therefore, experimental approaches to develop new therapeutic options for IBD are encouraged.…”
Section: Effects Of Decoy Odns On Expression Of Proinflammatory Cytokmentioning
confidence: 99%
“…Conventional therapies for IBD focus on suppression and control of inflammation using 5-aminosalicylates, corticosteroids, and immune-modulating drugs, such as azathioprine and mercaptopurine. [10][11][12][13][14] On the other hand, recently developed novel cytokine antagonist therapies targeting TNF-a and IL-6 have been found to be quite effective in certain IBD patients. [15][16][17][18] Such molecular targeted inhibition of inflammatory processes may provide better therapeutic options for IBD and studies have been conducted to evaluate new innovative approaches.…”
mentioning
confidence: 99%
“…Considering these inflammatory consequences, several conventional therapeutic approaches for IBD, mainly based on suppression and control of inflammation, have been proposed (8 -10). Also, recently developed novel cytokine antagonist therapies have been found to be effective in certain IBD patients (11)(12)(13). Such molecular targeted inhibition of the inflammatory process may provide better therapeutic options for IBD, and various studies have been conducted to evaluate new innovative approaches.…”
mentioning
confidence: 99%
“…MP inhibits many of the major immune pathways (13,51). MP and other glucocorticoids have been shown to reverse the inhibition of nutrient and electrolyte malabsorption in animal models of IBD or Crohn's disease (7,10,16,17,30,32,33,36,43,46). For example, we have demonstrated that SGLT1 (43), ASCT1 (46), and the Na-K-ATPase inhibition (43,46) are reversed by MP in a rabbit model of chronic ileal inflammation.…”
mentioning
confidence: 70%